Urgency of Marriage Registration for Women and Child Protection in Gayo Lues District - Hanapi, Agustin; Yuhermansyah, Edy (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
Announcing marriage is an act to spread Islamic greatness. There have never been any previous scholars who married secretly or did not announce their marriages. Currently, marriages that are carried out in secret are synonymous with elopement and are not recorded in the Religious Affairs Office. The phenomenon of underage elopement, which the locals refer to as ‘naik’ (rising), is quite prevalent in Gayo Lues District. There have been six cases occurred already in one year. A pair of students who were still under 19 without the permission of their parents or the school deliberately went to a traditional leader, begging to be married off, while some others even dared to skip the administrative procedures and directly married, thinking that the procedures could be taken care of later. However, the real-life is not as smooth as they expected, and so their marriage was not registered, eventually causing the women and children to be the victims. In this study, the focus has related the perspective of Islamic jurisprudence and legislation in Indonesia on marriage registration and the consequences for women and children when there is no marriage registration. This qualitative study used in-depth interviews, descriptive analysis methods, the empirical juridical approach, and the normative juridical approach. The results of the study showed that students who eloped in high school generally no longer continued their studies because of shame and inferiority towards their friends. Marriage registration is handled by the State or the Government through statutory regulations in order to create orderly marriage in society.